Invisible influence : the power to persuade anyone, any time, anywhere - Hogan, Kevin (Wiley, 2013)
Invisible Influence shows readers how to quietly persuade others to choose them or their product. The book includes new scientific discoveries in subtle influence that show a few fascinating and unique approaches to influence. The book will highlight how people feel about products, services and people, and the mental shortcuts they use to buy. It will then teach readers how to utilize this cluster of information in subliminally influencing others in order to sell, market, and communicate more effectively.